Analisis Aplikasi Moderasi Beragama Pada Pembelajaran Agama Islam - Yasmansyah, Yasmansyah; Iswantir, Iswantir; Movitaria, Mega Adyna (IQRO: Journal of Islamic Education, 2023)
The rise of fanatics and terrorist attacks carried out in the name of Islam is soaring rapidly around the world, especially in Indonesia, which poses a threat to religious freedom. Islam is still a target of criticism in the country, and jihadist dogma has been perverted into a pretext to exert pressure on Muslims under the guise of religion. The purpose of this study was to analyze the application of religious moderation in Islamic religious education at SMA Negeri 1 Batusangkar. The research method used is a qualitative method with a field study approach. The results of the study found that SMAN 1 Batusangkar can instill moderation in the student community, even students who have a religious disposition, very significantly. Some religious attitudes in students are firm, caring and fair.